Volatile aroma compounds of sugarcane molasses as affected by spray drying at low and high temperature. (June 2021) - Samborska, Katarzyna; Bonikowski, Radosław; Kalemba, Danuta; Barańska, Alicja; Jedlińska, Aleksandra; Edris, Amr
Abstract: Sugarcane molasses was chosen as an example material for the investigation of the influence of spray drying approach (conventional high temperature and a developed low temperature drying method which applies dehumidified air as a process gas) and the presence of drying carrier on volatile aroma compounds (VACs). Among 28 identified VACs 10 were chosen for detailed investigation. The influence of drying depended, apart from two mentioned factors, also on the type/origin of VACs and particle morphology. In the case of compounds connected with the fermentation process, the retention was higher after high temperature spray drying. On the contrary, VACs which could be additionally created during spray drying, thus Maillard reaction and caramelization reaction products, were more abundant in samples dried at lower temperature. As was explained, this contradictory phenomenon could be related to the higher evaporative loss at higher temperature, and also the fact that particles created at higher temperature were partially destroyed (as evident from the SEM photos). The presence of carrier increased the content of VACs after low temperature spray drying, which was connected to the encapsulation mechanisms of high molecular weight material. Thus, the most beneficial was the simultaneous application of carrier and low temperature spray drying approach. Highlights: High and low temperature spray drying were tested for impact on VACs. Ten VACs were chosen for detailed investigation. Low temperature spray drying was more beneficial for the retention of VACs. The application of carrier was beneficial for the retention of VACs. The type and origin of VACs also affected the retention during spray drying.